116k views
4 votes
Write the quadratic function in standard form.
f(x) = 6x^2 − x + 1

1 Answer

4 votes

Answer:

The equation in standard form is:


f(x)=6(x-(1)/(12))^2-(23)/(24)

Explanation:

Given function:


f(x)=6x^2-x+1

We need to convert this in standard form which is given by:


f(x)=a(x-h)^2+k

where
a represent co-efficient of leading term which is
x^2

and
(h,k) is the vertex (minimum and maximum point) of the curve.


h can be found out using formula
h=(-b)/(2a)


a=6\ and\  b=-1


h=(-(-1))/(2(6))=(1)/(12)

We can find
k by finding
f(h) as
k=f(h).


k=f((1)/(12))=6((1)/(12))^2-(1)/(12)+1


k=(6* (1)/(144))-(1)/(12)+1


k=(1)/(24)-(1)/(12)+1


k=(1-2+24)/(24)=(23)/(24)

Thus the equation in standard form is:


f(x)=6(x-(1)/(12))^2-(23)/(24)

User Alex Leach
by
5.8k points